The prioritization for higher education institutions performance criteria with Fuzzy Analytical Hierarchy Process - R. Wongsathan (2018)
© 2014 IEEE. This research is an investigation of criteria for making a decision of quality in the higher education institutions. The multi-criteria decision was used to achieve the progressive of quality in the university. Fuzzy Analytical Hierarchy Process (FAHP) is applied for these multi-criteria to select the highest prioritizing criteria for achieving the goal of quality institution which can tolerate vagueness and uncertainty of human judgment. The hierarchy consists of 9 main criteria and 44 sub-criteria, recognized by Office of the Higher Education Commission Ministry of Education Thailand, correspond with those main criteria and 6 alternatives from the experts under each sub-criterion. The sensitivity analysis has made by changing the membership function, from triangular membership function to trapezoidal membership function, the studied also changed membership number. However the result of this hypothesis has shown that none of functions variation has impacted the main criteria and alternative. The comparison of preference score and priority of each criterion between FAHP and AHP has the same results.